Improving EFL Students’ Grammar in Writing Sentences Using Mistake Buster Technique - Mohd. Rafi Riyawi; Zulfia Siska Wati (STAI Hubbulwathan Duri, 2023)
The purpose of this study was to determine the impact of using the mistake buster technique on grammar mastery for English writing classes. The research approach uses quantitative research through the design of a one-group experimental method. The research subjects were 30 semester III students for the 2022-2023 academic year, STAI Hubbulwathan Duri. Samples were taken randomly with the criteria that students had received English writing skills learning. So, this research was conducted at the English Tadris Study Program, STAI Hubbulwathan Duri. The data collection process uses observation, documents, and tests. Data analysis used paired sample t-test. The results of this study indicate that the mistake-buster technique has a positive influence on the ability to master grammar while learning to write English. This can be seen from the increase in the value achieved by each student or the class average value. Students experience a change in attitude to become more active during learning and can apply their learning experiences to make correct sentences. The results of this study also have implications for teachers' understanding of the importance of understanding learning techniques that are by learning objectives and student learning experiences.